Numerical analysis of 1/28 scaled NGNP HTGR reactor building test facility response to depressurization event using GOTHIC. (September 2018) - Yildiz, Mustafa Alper; Yang, Se Ro; Vaghetto, Rodolfo; Hassan, Yassin A.
Abstract: A depressurized loss of forced cooling (DLOFC) accident is an important type of accident scenario in high temperature gas reactor (HTGR) design, which is initiated by a break in the helium pressure boundary (HPB). This class of accident scenarios results in a depressurization of the primary helium coolant system with the subsequent release of helium into the reactor building (RB) and the atmosphere through vented low pressure containment (VLPC). After the total depressurization of helium, depending on the specific accident scenarios, it is also possible that air enters into the reactor pressure vessel (RPV) through the RB, which can potentially react with fuel and other nuclear-grade graphite components. In this study, generation of thermal hydraulic information in containments (GOTHIC) model of a 1/28-scaled simplified test facility was developed to analyze the depressurization scenarios and validate them against experimental data. Natural leakage from the test facility was modeled using two different methods. The post-depressurization refill of air into the test facility compartments along with two hypothetical depressurization scenarios were analyzed and compared with experimental data. In general, simulation results were observed to be consistent with the experimental data.